Pengaruh Promosi dan Diskon Terhadap Keputusan Pembelian di Marketplace Tiktok Shop - Alban Djordy; Ilhamuddin (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2026)
This study aims to determine the effect of promotions and discounts on purchasing decisions in the TikTok Shop marketplace. The type of research used is associative causal research with a quantitative approach. The sample size used in this study is 96 people, with data collected through a questionnaire method and determined using a nonprobability sampling technique with purposive sampling. The data collection technique involves first observing the object being studied, then administering a questionnaire to participants based on the criteria of individuals who have made transactions on the TikTok Shop marketplace in Mataram. The analysis tool used is Multiple Linear Regression Analysis, with the SPSS 16 for Windows program. The data analysis results show that; (1) promotions have a positive and significant effect on purchasing decisions, and (2) discounts have a positive and significant effect on purchasing decisions.